Dual functional and multiple substituted fluorescent star-shaped POSS for a 1 + 1 > 2 explosive vapour detection. Issue 56 (25th May 2016) - Gao, Yixun; Xu, Wei; Zhang, Xiangtao; Fu, Yanyan; Zhu, Defeng; He, Qingguo; Cao, Huimin; Cheng, Jiangong
Abstract : A dual functional and multiple substituted fluorescent star-shaped POSS was synthesized for highly efficient NG and TNT vapor detection. Abstract : A dual functional and multiple substituted fluorescent star-shaped POSS has been designed and synthesized. There is effective FRET between the different functional arms. Compared with a single functional probe, the dual functional POSS showed a much better sensing performance to explosive NG and a comparable performance to TNT vapor.